Navigating aspirations: the role of self-concept in shaping academic performance among diverse adolescents - Masinga, Nonhlanhla (Frontiers in Education, 2025)
This manuscript investigates the relationship between adolescents’ aspirations and academic performance, focusing on self-concept dimensions such as self-esteem, self-efficacy, and self-regulation. Using empirical data and a longitudinal design, the study examines how these elements of self-concept mediate the link between aspirations and academic success, with particular attention to adolescents from diverse socio-economic and cultural backgrounds in South Africa. Although the research is situated in a historically racialized educational system, the findings reveal that socio-economic disparities, rather than race alone, are key drivers of educational outcomes. By applying the lens of critical racial consciousness, this study highlights how systemic inequalities in schooling contexts interact with psychological factors to influence learner development. Findings showed that self-regulation, academic self-efficacy, and self-esteem were positively linked to performance. In addition, systemic inequalities such as resource deprivation, underfunding and curriculum marginalisation restricted students’ possibilities. The manuscript offers actionable insights for educators and policymakers by advocating for interventions that support self-concept development in under-resourced environments. It argues that fostering self-efficacy, self-regulation, and self-esteem is essential for enabling students to bridge the aspiration-attainment gap. Through the lens of critical racial consciousness, the manuscript contributes to the discourse on educational psychology and adolescent development by emphasizing the need for targeted interventions that consider the structural and social determinants shaping youth aspirations and achievement.